Peningkatan Strategi Pengembangan Usaha Ukm Kota Medan - surya asih (CERED Indonesia Institute, 2020)
The problem faced by Tegalwangi Furniture UKM is the existence that is less well known by the public due to limited marketing constraints. The purpose of this study was to determine the company's strategy in developing alternative Tegalwangi furniture using SWOT analysis. This research is a descriptive research with the support of qualitative data, data collection techniques are obtained through in-depth interviews with real data from internal and external fields. From the results obtained using SWOT analysis, there are 8 alternative strategies: (1) Maintaining product quality (2) Developing a business by serving sales to outside the region (3) Collaborating with Home Credit (4) Increasing promotion via the internet (5) Offering products to organization or work group (6) Improving the quality of service to customers (7) Increasing / providing creative and interesting product variations (8) Adding distribution channels